Integrating Cognitive Dysfunction Accommodation Strategies Into Behavioral Interventions for Persons on Medication for Opioid Use Disorder - Mistler, Colleen B.; Idiong, Christie I.; Copenhaver, Michael M. (Frontiers in Public Health, 2022)
Background: Cognitive dysfunction is disproportionately prevalent among persons with opioid use disorder (OUD). Specific domains of cognitive dysfunction (executive functioning, attention, memory, and information processing) may significantly impede treatment outcomes among patients on medication for OUD (MOUD). This limits patient's ability to learn, retain, and apply information taught in behavioral intervention sessions. Evidence-based accommodation strategies have been integrated into behavioral interventions for other patient populations with similar cognitive profiles as persons with OUD; however, the feasibility and efficacy of these strategies have not yet been tested among patient on MOUD in a drug treatment setting. Methods: We conducted a series of focus groups with 25 key informants (10 drug treatment providers and 15 patients on MOUD) in a drug treatment program in New Haven, CT. Using an inductive approach, we examined how cognitive dysfunction impedes participants’ ability to retain, recall, and utilize HIV prevention information in the context of drug treatment. Results: Two main themes capture the overall responses of the key informants: (1) cognitive dysfunction issues and (2) accommodation strategy suggestions. Subthemes of accommodation strategies involved suggestions about particular evidence-based strategies that should be integrated into behavioral interventions for persons on MOUD. Specific accommodation strategies included: use of a written agenda, mindfulness meditation, multimodal presentation of information, hands-on demonstrations, and a formal closure of sessions. Conclusions: Accommodation strategies to compensate for cognitive dysfunction were endorsed by both treatment providers and patients on MOUD. These accommodation strategies have the potential to enhance the efficacy of behavioral interventions to reduce HIV transmission among persons on MOUD as well as addiction severity, and overdose.